VraR Binding to the Promoter Region of agr Inhibits Its Function in Vancomycin-Intermediate Staphylococcus aureus (VISA) and Heterogeneous VISA - Dai, Yuanyuan (Antimicrob Agents Chemother, 2017)
Acquisition of vancomycin resistance in Staphylococcus aureus is often accompanied by a reduction in virulence, but the mechanisms underlying this change remain unclear. The present study was undertaken to investigate this process in a clinical heterogeneous vancomycin-intermediate S. aureus (hVISA) strain, 10827; an hVISA reference strain, Mu3; and a VISA reference strain, Mu50, along with their respective series of vancomycin-induced resistant strains. In these strains, increasing MICs of vancomycin were associated with increased expression of the vancomycin resistance-associated regulator gene (vraR) and decreased expression of virulence genes (hla, hlb, and coa) and virulence-regulated genes (RNAIII, agrA, and saeR). These results suggested that VraR might have a direct or indirect effect on virulence in S. aureus. In electrophoretic mobility shift assays, VraR did not bind to promoter sequences of hla, hlb, and coa genes, but it did bind to the agr promoter region. In DNase I footprinting assays, VraR protected a 15-nucleotide (nt) sequence in the intergenic region between the agr P2 and P3 promoters. These results indicated that when S. aureus is subject to induction by vancomycin, expression of vraR is upregulated, and VraR binding inhibits the function of the Agr quorum-sensing system, causing reductions in the virulence of VISA/hVISA strains. Our results suggested that VraR in S. aureus is involved not only in the regulation of vancomycin resistance but also in the regulation of virulence.